Urbanization drives riverine bacterial antibiotic resistome more than taxonomic community at watershed scale. (April 2020) - Peng, Feng; Guo, Yunyan; Isabwe, Alain; Chen, Huihuang; Wang, Yongming; Zhang, Yanping; Zhu, Zhenxiang; Yang, Jun
Graphical abstract: Highlights: ARG richness and abundance in waters increased from rural to urban regions. ARGs profiles showed a temporal stability in downstream waters over five years. Deterministic and stochastic processes mainly shaped ARGs and OTUs, respectively. Bacterial function and taxonomy community were decoupled in urbanizing watershed. Progressive urbanization promotes the enrichment and stability of ARGs in waters. Abstract: Although the occurrence and distribution of antibiotic resistance genes (ARGs) in various aquatic ecosystems are well explored, understanding of the ecological processes and mechanisms governing the composition and dynamics of bacterial ARGs still remains limited across space and time. Here, we used high-throughput approaches to detect spatial patterns of bacterial ARGs and operational taxonomic units (OTUs) in an urbanizing subtropical watershed, Xiamen, southeast China over a five-year period. At watershed scale, the OTU profiles were undergoing a directional change, but the ARG profiles showed a high stability or stochastic change over time. Compared with the upstream and midstream, the richness, absolute abundance, normalized abundance and diversity of ARGs were significantly higher in the downstream waters. Our results revealed a clear rural-urban disparity in ARG and OTU profiles which were mainly governed by deterministic and stochastic assembly processes, respectively. With the increase of urban building area along the river, the ecological processes of ARG profiles shifted from stochastic to deterministic. In downstream waters, the bacterial ARG profiles were much more stable than bacterial OTUs. Further, our results indicated that both human-dominated environment (e.g., land use) and mobile genetic elements (MGEs) played an important role in shaping the ARG profiles and dynamics. Overall, this was a response to spatially extensive human-landscape interactions that included urban development in the river downstream region, which were common across subtropical coastal cities of China and can alter the ARG profile dynamics along rural-urban gradient. Therefore, watershed management actions aiming at reducing threats posed by ARGs in urbanizing watershed should first consider the surrounding urbanization level and the mode and intensity of human activity. Our findings also imply that due to the decoupling of bacterial function and taxonomy, both aspects should be studied separately.